CD95 recruits PLCγ1 to trigger a calcium response promoting Th17 accumulation in inflamed organs of lupus mice - Poissonnier, Amanda; Sanseau, Doriane; Le Gallo, Matthieu; Malleter, Marine; Levoin, Nicolas; Viel, Roselyne; Morere, Lucie; Penna, Aubin; Blanco, Patrick; Dupuy, Alain; Poizeau, Florence; Fautrel, Alain; et al. (Elsevier, 2016)
CD95 ligand (CD95L) is expressed by immune cells and triggers apoptotic death. Metalloprotease-cleaved CD95L (cl-CD95L) is released into the bloodstream but does not trigger apoptotic signaling. Hence, the pathophysiological role of cl-CD95L remains unclear. We observed that skin-derived endothelial cells from systemic lupus erythematosus (SLE) patients expressed CD95L, and that after cleavage, cl-CD95L promoted T helper 17 (Th17) lymphocyte transmigration across the endothelial barrier at the expense of T regulatory cells. T cell migration relied on a direct interaction between the CD95 domain called calcium-inducing domain (CID) and the Src homology 3 domain of phospholipase Cγ1. Th17 cells stimulated with cl-CD95L produced sphingosine-1-phosphate (S1P), which promoted endothelial transmigration by activating the S1P receptor 3. We generated a cell-penetrating CID peptide that prevented Th17 cell transmigration and alleviated clinical symptoms in lupus mice. Therefore, neutralizing the CD95 non-apoptotic signaling pathway may be attractive therapeutic approach for SLE treatment.